Comunidades quilombolas: as lutas por reconhecimento de direitos na esfera pública brasileira - Santos, Simone Ritta dos (2012)
The theme of this study is the emergence of ethnic discourses and the struggles for recognition of the rights of the Quilombo communities in the contemporary Brazilian context. The research, which is in qualitative nature, favors the analysis of the meanings that individuals give their actions, in the space in which they build their lives and their relationships, as well as the broader social context in which these relationships occur. It is descriptive in nature and uses multiple sources and a variety of tools and techniques for gathering information. The technical procedures include a mix of elements from a field study such as participant observation, interviews and analysis of documents and bibliographies. The aim of this study is to reflect on the construction of knowledge of the Quilombo- communities, from a multidisciplinary socio-historical and anthropological theoretical perspective, which seeks to reveal the dialectic of discourses on equality and difference, found in Brazilian public sphere in the context of struggles for recognition of ethnic rights. The issues guiding this thesis refer to the historical constitution of discourses between actors in the public sphere in the implementation of rights for the Quilombola population in Brazil, seeking to analyze the tension between the notions of equality and difference, in the formulation of public policies in the Brazilian state, in order to identify the interests and political projects in dispute in the context of the rights of these populations. The results of this study show that the struggle for recognition of the rights of the Quilombo communities must be understood in the light of the phenomenon of ethnicity, to the extent that there is a process an identity that is built is demarcated, in the political field, by affirming difference while in the quest for equality. The affirmation of differences requires that the subjects relinquish the use of multiple strategies (legal, bureaucratic, economic, political, scientific), since, in the struggle of classifications, relations of power (material and symbolic) are imposed between the various interests at stake. Such interests, in the Quilombola field, are mediated by the discourses and practices of agents who ― "play" with classifications of what may be equality, difference, or what may be remaining in a dynamic and relational process.